2018
DOI: 10.1007/s00264-018-4139-9
|View full text |Cite
|
Sign up to set email alerts
|

Surgical approach for open reduction and internal fixation of clavicle fractures: a comparison of vertical and horizontal incisions

Abstract: Vertical incision results in shorter scars but may be associated with increased incidence of haematomas. Meticulous closure of the subcutaneous tissue is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Common complications of plate fixation include implant-related symptoms, sensory deficits, wound infections, and nonunion. [63][64][65] In adults, 5.6-25% of patients may require a secondary operation for implant removal due to irritation. 63,[66][67] Intramedullary fixation may result in irritation at the entry site due to the protruding end of the nail.…”
Section: Complicationsmentioning
confidence: 99%
“…Common complications of plate fixation include implant-related symptoms, sensory deficits, wound infections, and nonunion. [63][64][65] In adults, 5.6-25% of patients may require a secondary operation for implant removal due to irritation. 63,[66][67] Intramedullary fixation may result in irritation at the entry site due to the protruding end of the nail.…”
Section: Complicationsmentioning
confidence: 99%
“…[ 67 , 68 , 69 , 70 , 71 ]. Either a longitudinal incision along the subcutaneous border of the clavicle or a vertical (necklace) incision along the Langer lines may be used for osteosynthesis using pre-contoured plates, although smaller skin incisions may be used in a minimally invasive approach with plate osteosynthesis or intramedullary fixation devices [ 72 , 73 , 74 , 75 ]. Unstable distal fractures may further require coracoclavicular repair, tension-band wiring, reconstruction, hook plating, or transacromial pinning [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…( Appendix I ) [ 11 , 19 , 23 36 ]. However, this rate increases to 52% when the affected area is measured as part of the study protocol suggesting a possibility of under reporting [ 29 , 34 , 36 ]. We report a larger affected size (36.6 cm 2 [+/− 26.9 cm 2 ]) than the weighted average of 26 cm 2 previously reported in the literature, though the variability seen in our findings represents the challenge inherent to patients’ self-estimation.…”
Section: Discussionmentioning
confidence: 99%
“…Fifteen studies, including 836 patients, reported on average, when weighted, a 27% incidence of numbness at approximately 28 months following longitudinal approach to plate fixation of acute clavicle diaphyseal fractures. (Appendix I) [11,19,[23][24][25][26][27][28][29][30][31][32][33][34][35][36]. However, this rate increases to 52% when the affected area is measured as part of the study protocol suggesting a possibility of under reporting [29,34,36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation